Social Criticism about the 2019 Election Campaign in the Comic Strip Gump n Hell - Luqman Wahyudi; Sri Hesti Heriwati (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Comic strips are a top-rated entertainment product. Supported by growing information technology, comic strips today are very accessible to almost all people. In addition to serving as a medium of entertainment, comic strips are often used as a means of opinion and convey criticism creatively from the comic artist. One of the comic strips that are vocal in expressing social criticism is Gump n Hell comic strip by Errik Irwan Wibowo. This comic strip depicts political events that occur, then publishes the comics through social media. This research is qualitative descriptive research using Charles Sanders Peirce's semiotic theory to determine the meaning of social criticism in the comic strip Gump n Hell. The researcher took three Gump n Hell comic strip samples relating to the moment of the 2019 General Election to analyzed the meaning. From the study results, there was an implicit meaning in the comic strip, namely criticizing and satirizing specific political figures related to the phenomenon. Criticism in comics is represented subtly or indirectly through pop culture icons that become representations or parodies of exact political figures and wrapped in narratives according to political phenomena.